Predictors and long-term reproducibility of urinary phthalate metabolites in middle-aged men and women living in urban Shanghai. (November 2015) - Starling, Anne P.; Engel, Lawrence S.; Calafat, Antonia M.; Koutros, Stella; Satagopan, Jaya M.; Yang, Gong; Matthews, Charles E.; Cai, Qiuyin; Buckley, Jessie P.; Ji, Bu-Tian; Cai, Hui; Chow, Wong-Ho; et al.
Abstract: Phthalate esters are man-made chemicals commonly used as plasticizers and solvents, and humans may be exposed through ingestion, inhalation, and dermal absorption. Little is known about predictors of phthalate exposure, particularly in Asian countries. Because phthalates are rapidly metabolized and excreted from the body following exposure, it is important to evaluate whether phthalate metabolites measured at a single point in time can reliably rank exposures to phthalates over a period of time. We examined the concentrations and predictors of phthalate metabolite concentrations among 50 middle-aged women and 50 men from two Shanghai cohorts, enrolled in 1997–2000 and 2002–2006, respectively. We assessed the reproducibility of urinary concentrations of phthalate metabolites in three spot samples per participant taken several years apart (mean interval between first and third sample was 7.5 years [women] or 2.9 years [men]), using Spearman's rank correlation coefficients and intra-class correlation coefficients. We detected ten phthalate metabolites in at least 50% of individuals for two or more samples. Participant sex, age, menopausal status, education, income, body mass index, consumption of bottled water, recent intake of medication, and time of day of collection of the urine sample were associated with concentrations of certain phthalate metabolites. The reproducibility of an individual's urinary concentration of phthalate metabolites across several years was low, with all intra-class correlation coefficients and most Spearman rank correlation coefficients ≤ 0.3. Only mono(2-ethylhexyl) phthalate, a metabolite of di(2-ethylhexyl) phthalate, had a Spearman rank correlation coefficient ≥ 0.4 among men, suggesting moderate reproducibility. These findings suggest that a single spot urine sample is not sufficient to rank exposures to phthalates over several years in an adult urban Chinese population. Highlights: We identify predictors of urinary phthalate metabolites in an urban Chinese cohort. The reproducibility of phthalate metabolite concentrations over 2–8 years was low. A single spot urine sample may be insufficient to rank exposures over years.